Determination of glycosaminoglycans in biological matrices using a simple and sensitive reversed-phase HPLC method with fluorescent detection - Braun, Martin; Rýglová, Šárka; Suchý, Tomáš (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2021)
This paper suggests a sensitive reversed-phase gradient HPLC method combined with fluorescence detection that has been developed, optimized and tested via the quantitative analysis of authentic biological material in an effort to determine and subsequently compare the total content of glycosaminoglycans (GAGs) in various collagen-based biomaterials intended for medical application. The proposed analytical method enabled the identification and separation of the GAGs present from the other components in the samples using commonly-available laboratory equipment; moreover, the very low detection limit of the method permits the determination of GAGs even for very small samples. This study describes the development of the method, including the isolation and processing of the collagen samples prior to HPLC analysis and the optimal parameters applied during the chromatographic analysis. The application of the method in laboratory practice is documented by means of several examples of the determination of GAGs employing both commercial standards and real collagen samples isolated from various animal tissues.
Keywords: Analysis; Derivatization; Fluorescent detection; Glycosaminoglycan; HPLC; Collagen